A short review on the trend of mobile marketing studies - Razli Che Razak; Mohammad Ismail (2011)
The purpose of this paper is to elucidate the major classification of the research in mobile marketing. It provides the trend and common approach in mobile marketing research. The paper aims to highlight the significant area in mobile marketing research and the needs for further understanding of the mobile marketing definition and its phenomenon. This paper has significant implications in terms of understanding the classification and the mobile marketing focusing area. This is a general review based on selected approximately forty-six journal publications which are published between year 2005 until 2010 from selected journals. Based on the selected reviewed literatures, the consumers’ adoption research only focuses on a few common areas. There is no agreement among the researchers on definition of mobile marketing and the conceptualization and phenomenon of mobile marketing remain unexplained. The value of this paper is that, it provides the fundamental guidelines for researchers on significant area to focus in the mobile marketing field and it also assists practitioners in identifying the research trend and major classifications which will assist them in designing the product and services to the right target market.